MicroRNAs miR-30b, miR-30d, and miR-494 Regulate Human Endometrial Receptivity - Altmäe, Signe; Martinez-Conejero, Jose A.; Esteban, Francisco J.; Ruiz-Alonso, Maria; Stavreus-Evers, Anneli; Horcajadas, Jose A.; Salumets, Andres (Reproductive sciences (Thousand Oaks, Calif.), 2013)
MicroRNAs (miRNAs) act as important epigenetic posttranscriptional regulators of gene expression. We aimed to gain more understanding of the complex gene expression regulation of endometrial receptivity by analyzing miRNA signatures of fertile human endometria. We set up to analyze miRNA signatures of receptive (LH + 7, n = 4) versus prereceptive (LH + 2, n = 5) endometrium from healthy fertile women. We found hsa-miR-30b and hsa-miR-30d to be significantly upregulated, and hsa-miR-494 and hsa-miR-923 to be downregulated in receptive endometrium. Three algorithms (miRanda, PicTar, and TargetScan) were used for target gene prediction. Functional analyses of the targets using Ingenuity Pathways Analysis and The Database for Annotation, Visualization and Integrated Discovery indicated roles in transcription, cell proliferation and apoptosis, and significant involvement in several relevant pathways, such as axon guidance, Wnt/β-catenin, ERK/MAPK, transforming growth factor β (TGF-β), p53 and leukocyte extravasation. Comparison of predicted miRNA target genes and our previous messenger RNA microarray data resulted in a list of 12 genes, including CAST, CFTR, FGFR2, and LIF that could serve as a panel of genes important for endometrial receptivity. In conclusion, we suggest that a subset of miRNAs and their target genes may play important roles in endometrial receptivity.